COST BUDGET PLAN AND REVENUE PROJECTIONS ON GRAVIS STARTUPS - Syadza Adilah Malsuf; Khairunnisa Khairunnisa (Inovbiz: Jurnal Inovasi Bisnis, 2022)
Gravis is a startup as a connector platform between freelancer design and business actors who need visual communication services. The background to the founding of Gravis is the COVID-19 pandemic that had hit Indonesia for two years and affected all aspects of people's lives in terms of health, social, psychology, and especially the economy. As a result, people are forced to shift their activities from offline to online methods with the urgency to maintain social distancing to avoid direct physical and social contact. This condition changes everything that is non-digital to digital, and information packaging has increased visually. In this case, the Visual Communication Design subsector has an important role in carrying it out. Gravis was founded as a startup that overcomes these problems. In establishing a Gravis startup, of course, Gravis must make a budget plan and revenue targets to support Gravis' operations and sustainability. However, because the business model owned by startups tends to be unique and different from conventional companies in general, various adjustments are needed. This journal aims to adjust the steps and formats used in making cost budget plans and startup revenue projections according to the needs and business models owned by startups, especially Gravis